Japanese Religions and Globalization. - Dessì, Ugo (Taylor and Francis, 2013)
This book analyzes the variety of ways through which Japanese religions (Buddhism, Shint?, and new religious movements) contribute to the dynamics of accelerated globalization in recent decades. It looks at how Japanese religions provide material to cultural global flows, thus acting as carriers of globalization, and how they respond to these flows by shaping new glocal identities. The book highlights how, paradoxically, these processes of religious hybridization may be closely intertwined with the promotion of cultural chauvinism. It shows how on the one hand religion in Japan is en.